A lean six sigma framework for identifying sources of waste in manufacturing sector in Indonesia - Kholil, Muhammad (2022)
Manufacturing activities until the beginning of 2020 shows an increment and continue to grow at 210 trillion value or contributes 30.4 percent of Indonesia's investment. Therefore, manufacturing companies need to create an appropriate system to support demand in this sector. In this research, the define-measure-analysis-identify-control (DMAIC) model, value stream mapping (VSM), and value stream analysis tool (VALSAT) are integrated in conducting an in-depth analysis for identifying the sources of waste in 33 manufacturing companies around the Java Islands. There are three main wastes can be identified, namely, (i) defects, (ii) inappropriate processes, and (iii) waiting time. In order to minimize the waste, several solution steps for the root cause error were proposed. Based on man & material root cause error, an adequate training and education need to be provided to all employees in production and non-production. Based on method root cause error, it is necessary to regularly establish standard operating procedures with a clear work instruction, and followed by periodic procedure review. In this category, it is also suggested to develop a specific procedure for predictive and preventive maintenance of an engine factor. Based on environmental root cause error, the manufacturing company need to reinspect the condition of the work location and area to store raw materials and finished goods. In general, this research has provided a new perspective in realizing minimum waste practice in the manufacturing sector.